INTEGRASI PENGEMBANGAN DAN ETIKA DIGITAL DALAM PEMANFAATAN CANVA SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Jefpi Milda; Aqila Muthmainna; Karoma Karoma; Muhammad Isnaini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the integration of media development and digital ethics in the utilization of Canva as a learning media for Islamic Religious Education (PAI) in the digital era. The purpose of this research is to analyze how Canva can be effectively used as a PAI learning tool while applying digital ethics principles in accordance with Islamic values. This study employs a library research method by collecting data through the review of books, journals, scientific articles, and digital documents related to learning media, educational technology, and digital ethics. The data obtained were analyzed qualitatively to identify concepts, principles, and best practices in using Canva in PAI classrooms. The results indicate that Canva enables teachers to present abstract materials in a visual, engaging, and interactive manner, thereby enhancing students’ understanding and learning motivation. Moreover, the application of digital ethics ensures that media usage remains aligned with moral values and Islamic character, making PAI learning effective, creative, and responsible.